Virtues as Correlates and Predictors of Posttraumatic Stress and Growth. Issue 2 (1st October 2021) - Zeligman, Melissa; Norris, Elizabeth K.; Coleman, Jamian; Wood, Andrew W.
Abstract : We examined the virtues of optimism, hope, and gratitude as potential correlates and predictors of posttraumatic stress (PTS) and posttraumatic growth (PTG) in a sample of trauma survivors ( N = 151). Results indicated that each of these qualities significantly correlated with PTS and PTG. Hierarchical regression analyses revealed that optimism, hope, and gratitude each significantly predicted PTS, with hope being the greatest predictor of PTG. Clinical implications for professional counselors are discussed.